Principles Of The Development Of Islamic Educational Objectives - Muhammad Khusna Syah; Fakhrin Aeni Salsabila; Mahwiyah (Amandemen: Journal of Learning, Teaching and Educational Studies, 2023)
The purpose of Islamic education is something that is expected to be achieved after the educational process ends. These objectives are classified into: general objectives, interim objectives, final objectives and operational objectives. I Islamic education can be used as a foundation to stem negative things and improve the moral behavior and character of this nation. In Islamic education it also invites to be patient, trust, love others, love and help each other, as many have explained in the Al-Quran and Hadith as examples for improvement for people who always do bad deeds. However, the development of thinking about the goals of Islamic education has never deviated from the basic principles which are the basis for developing the intended educational goals. Among these principles are universal, balance, clarity, dynamic, and relevant. So, the final formulation of Islamic education above can still be summarized again to become a human being who has a complete Muslim personality both physically and mentally who is able to devote all his deeds to seek the pleasure of Allah SWT.